Emotions and the oral development of teenage students of english as an additional language - Machado, Tamires Maria Rocha (Universidade do Vale do Rio dos Sinos, 2022)
Additional language learning and its relationship with emotions has been an ongoing research topic over the past decades, and it has been discussed by many authors (ARAGÃO, 2007, 2008, 2011, 2017; ARNOLD, BROWN, 1999; ARNOLD, 2011; BARCELOS, 2006, 2015; ROSIEK, 2003; VYGOTSKY, 1997 (originally published in 1926); VYGOTSKY, VAN DER VEER, VALSINER, 1994). Furthermore, authors have also vastly researched language learning anxiety (GREGRERSEN, HORWITZ, 2002; GREGERSEN, 2003; ELAINE HORWITZ, MICHAEL HORWITZ, JOAN COPE, 1986; HORWITZ, 2001; SILVEIRA, 2020; YOUNG, 1991) in the fields of Education and Applied Linguistics. Another popular research topic is the concept of perezhivanie (MOK, 2017; VERESOV, 2019; VYGOTSKY, 1994), which may not have a literal and exact translation, but is often translated as “emotional experience”. In that sense, the present study aims at analyzing (a) what pedagogical practices seem to promote emotions that hinder or improve learners’ oral development; (b) if (and how) teenage learners of English try to overcome their negative emotions while communicating in the target language. The methodological procedures included the elaboration of collages by the participants, as well as semi-structured interviews related to the collages and the participants’ emotions and experiences. The results indicated at participants’ level of awareness of their own emotions, as well as to a close connection between students’ emotions and activities which allow for emotional scaffolding.
Keywords: Aprendizagem de línguas adicionais; Emoções; Emoções negativas; Inglês; Desenvolvimento oral; Additional language learning; Emotions; Negative emotions; English; Oral development